The Influence of Corporate Governance, Bankruptcy Risk on Financial Performance and Company Value - Susanto, Antoni; Saifi, Muhammad; Imamah, Nur (Profit: Jurnal Adminsitrasi Bisnis, 2025)
This research aims to determine how corporate governance and bankruptcy risk affect financial performance and company value in non-financial companies listed on the IDX LQ-45 Index between 2019 and 2023. This research examines 18 non-financial organizations using the method quantitative methodology. This research uses a purposive sampling technique on companies that meet the BEI LQ-45 index criteria and provides comprehensive financial reports, corporate governance reports, ratios and other relevant data. Secondary data was collected from financial reports published by non-financial companies between 2019 and 2023—quantitative statistical analysis with PLS-SEM to test the research hypothesis. The research results show that, in the LQ-45 Index Companies listed on the Indonesia Stock Exchange from 2019 to 2023, Corporate Governance and Bankruptcy Risk had a positive and significant effect on Financial Performance, Corporate Governance and Bankruptcy Risk has a positive and not significant effect on Company Value,  and Financial Performance has a positive and significant effect on Company Value.